Efficacy of Pneumatic Lithoclast in Management of Different Metabolic Stones in Lower Ureter - Muhammad Umer, Ahsan Ayub, Aneela Jumadin, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Management of ureteral calculi represents one of the complex problems in urological practice. Aim: To study the efficacy of pneumatic lithoclast as a management option for different metabolic ureteric stones. Study design: Descriptive study. Methodology: Study enrolled both male and female patients (n=60) above 12 years of age. Stone size and metabolic type was determined with determining the Hounsfield units of the stone on plain abdominal CT scan and matching them with the predetermined ranges for specific stone types. Renal transplant and cancer patients were excluded. SPSS v.26 analyzed the data. Mean±SD presented quantitative variables. Results: Calcium oxalate stones were most frequent and were observed in 32 (53.3%) patients followed by Struvite (18.3%). Almost 96.7% ureteric stones were cleared with pneumatic lithoclast. Conclusion: It was concluded that pneumatic lithoclast is an efficacious procedure in urology in clearing different metabolic stones in lower ureter thus advocates its routine use. Keywords: Pneumatic Lithotripsy, Metabolic Stones and Ureteric Stone.